PENGARUH KARAKTER GANBARU TERHADAP ETOS KERJA PADA EKS-PEMAGANG DI JEPANG - Tri Mulyani Wahyuningsih (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2017)
The number of Indonesian workers who work abroad especially to Japan has given different working experience. These former apprentices intensively interacted with the Japanese who are working in Japanese firms so that they had little effect on the apprenticesâ€™ character. This study aims to describe how the work experience of the ex-apprentice in Japan has an effect on working ethic with the concepts of working culture in Japan especially ganbaru concept, after they returned to Indonesia. The approach used in this study is qualitative ethnographic. The results show that the experience of working with Japanese people influences the ex-apprenticesâ€™ character. The most influential concept is the culture of ganbaru (unyielding). The effect is seen in the time the ex-apprentices starts a business, they faced business constraints and they find a solution to be able to expand its business. Â Keywords: former apprentices, ganbaru character, influence, working ethic